Risk factors and causes of mortality after total correction for tetralogy of Fallot - Saylam, Argun; Olga, Rüstem; İkizler, Coşkun and Ertuğrul, Ali and Aytaç, Aydın (The Turkish Journal of Pediatrics, 1982)
Of 322 patients undergoing total correction for tetralogy of Fallot by the authors of this article, 47 died (14.5%). Operative mortality was 2.1%, hospital mortality 11.8% and late mortality 0.6%. Cardiac failure and low cardiac output syndrome were the most common causes of death after total correction. Risk factors and causes of mortality after total correction for tetralogy of Fallot are reviewed.